Effect of paleoseawater composition on hydrothermal exchange in midocean ridges - Antonelli, Michael A. (Proc Natl Acad Sci U S A, 2017)
Variations in the Mg, Ca, Sr, and SO(4) concentrations of paleoseawater can affect the chemical exchange between seawater and oceanic basalt in hydrothermal systems at midocean ridges (MOR). We present a model for evaluating the nature and magnitude of these previously unappreciated effects, using available estimates of paleoseawater composition over Phanerozoic time as inputs and (87)Sr/(86)Sr of ophiolite epidosites and epidote-quartz veins as constraints. The results suggest that modern hydrothermal fluids are not typical due to low Ca and Sr relative to Mg and SO(4) in modern seawater. At other times during the last 500 million years, particularly during the Cretaceous and Ordovician, hydrothermal fluids had more seawater-derived Sr and Ca, a prediction that is supported by Sr isotope data. The predicted (87)Sr/(86)Sr of vent fluids varies cyclically in concert with ocean chemistry, with some values much higher than the modern value of ∼0.7037. The seawater chemistry effects can be expressed in terms of the transfer efficiency of basaltic Ca and Sr to seawater in hydrothermal systems, which varies by a factor of ∼1.6 over the Phanerozoic, with minima when seawater Mg and SO(4) are low. This effect provides a modest negative feedback on seawater composition and (87)Sr/(86)Sr changes. For the mid-Cretaceous, the low (87)Sr/(86)Sr of seawater requires either exceptionally large amounts of low-temperature exchange with oceanic crust or that the weathering flux of continentally derived Sr was especially small. The model also has implications for MOR hydrothermal systems in the Precambrian, when low-seawater SO(4) could help explain low seawater (87)Sr/(86)Sr.